Human rights in the mining & metals industry : handling and resolving local level concerns & grievances. (International Council on Mining and Metals, 2009)
This publication sets out good practice approaches to help companies design and/or enhance existing complaint procedures or mechanisms. This publication aims to describe a set of 'overarching design principles' that provide basic, high-level guidance for companies developing complaints mechanisms; outline some basic criteria to help operations 'assess the nature of and potential for complaints' and so to develop a mechanism most appropriate to their situation; present three possible types of mechanism with incrementally greater levels of external engagement; and set out various ways in which global headquarters of companies can develop 'group-wide procedures' to support best practice locally. The main audience for the guidance is ICMM members and other interested companies in the mining industry.